Awareness and Implications of Constructive Dismissal Amongst Malaysia\'s Workforce: Perspective of Employers and Employees - Gaganathan, Liana Jacinta (2010)
This study examines the perplexing and yet important issue of constructive dismissal and explores the issues involving constructive dismissal in Malaysia by providing an indepth study of perspectives in various levels ranging from employers, employees, legal sector, unions and individuals.